In-Vitro the Anti-Protozoal Activity of Onions Extract (Allium Cepa) and Metronidazole in Entamoebagingivalis Which Cultured in Tysgm-9 Medium - Raflaa S.H. Hussian (Journal of Global Pharma Technology, 2017)
Entamoebagingivalis ( E. gingivalis )is an amoebae that is present in the human oral cavity associated with poor oral hygiene and advanced periodontal disease. The aim of the present study is to confirm antiprotozoal activity of Onions extract and metronidazole in E. gingivalis which cultured in TYSGM-9 medium as well as determinethe frequency of this among patients with periodontitisdisease. The study included 46 sample collected from patient with age (11-20) years, result show infection with this parasite 56.5 %. These samples are cultured in TYSGM-9 media, and then treated with Onions extract (Allium cepa) and metronidazole which show inhibited growth of parasite at 100μg/ml. Keywords: Entamoebagingivalis, Allium cepa, Metronidazole